Antecedentes do modelo de aceitação tecnológica (TAM) em plataformas que coletam dados pessoais dos usuários - Fridori , Matheus Sparapan (2024)
Individuals use several technological platforms daily, even knowing that these platforms may collect and use their personal data for commercial purposes. This study elaborated an adaptation of the Technology Acceptance Model (TAM), which has been empirically developed and tested in various contexts, replicated by several academic works. The model was analyzed through the privacy paradox theory, as people claim not to want to share personal information, but, in practice, end up settling this situation. The aim of this study is to understand the effects of the antecedents Number of users perception and Perceived value on the acceptance of the use of digital platforms, related to the sharing of data with technologies that collect consumer data and trade this information with online advertisers. For this purpose, we conducted a survey with a contact base obtained through digital ads (Google and Facebook) provided by an advertising company for these technologies. The sample was expanded using the snowball technique, resulting in 254 valid questionnaires for the study. The results of the data analysis indicated that perceived value and number of users perception positively influence the perceived usefulness of using these tools. However, the intention to use does not translate into an intention to share data with these tools, revealing a low willingness of users to provide their personal information for commercial purposes. These findings suggest that users value the benefits and convenience that digital platforms offer but do not intend to share data, accepting this condition only to enjoy the technology. Understanding these effects allows new technologies to use this information to obtain such data while ensuring user protection, enabling digital advertisers to continue targeting ads based on each user’s profile, and making users aware of these influences regarding their online behavior.